Emancipação ou ideologia?: uma análise da matriz curricular da rede municipal de ensino de Sorocaba - Pereira, Sara Aparecida (2016)
The development of this research, which has the object of study being the Curricular Matrix of Sorocaba's Education Municipal System sought through the documental analysis in a emancipatory education perspective. In this perspective the curriculum must be the way that builds the transformation possibility with the individuals. The concepts reviewed in this research were the ideology and emancipation, substantiated by the Critical Theory and the Humanizing Education. All of the concepts here introduced were discussed related to the Curricular Matrix of Sorocaba's Education Municipal System construction in order to analyse this document from a perspective of an education that effectively contributes to the emancipation of the individuals which is indeed committed to reality transformation. The methodology of this research sought to involve itself with the reality understanding, not a neutral understanding, but a ethically oriented one. To seek the answers for the research's problems, the document's analysis was created. The analysis took us to issues and discussions related with the theoretical foundations of this research and unveiling as for the ideological use of the emancipation concept. In the analysis it considered that by the use of the critical reading of documents which underlie education it is possible to realize the ideology diffusion, since a lot of documents make use of the emancipation concept in a ideological manner to mask its genuine conception, hampering the curriculum and education's understanding in a emancipation perspective. Many documents present a false speech of freedom and individuals emancipation, but if you read it critically and through the document's analysis, based on genuine references committed with the emancipatory education it is possible to reveal the intention of instill into the consciences false ideas for accepting things as they are, in other words, adjust men to the reality. The analysis developed revealed the ideological use and the ideological appropriation of the emancipation concept.